No association of IL-12p40 pro1.1 polymorphism with juvenile idiopathic arthritis. Issue 1 (December 2015) - Eberhardt, Christiane; Haas, Johannes-Peter; Girschick, Hermann; Schwarz, Tobias; Morbach, Henner; Rösen-Wolff, Angela; Foell, Dirk; Dannecker, Guenther; Schepp, Carsten; Ganser, Gerd; Honke, Nora; Eggermann, Thomas; et al.
Abstract Background IL-12p40 plays an important role in the activation of the T-cell lines like Th17 and Th1-cells. Theses cells are crucial in the pathogenesis of juvenile idiopathic arthritis. A polymorphism in its promoter region and the genotype IL12p40 pro1.1 leads to a higher production of IL-12p40. We studied whether there is a difference in the distribution of the genotype in patients with JIA and the healthy population. Methods In 883 patients and 321 healthy controls the IL-12p40 promoter genotype was identified by ARMS-PCR. Results There is no association of IL-12p40 pro polymorphism neither in patients with JIA compared to controls nor in subtypes of JIA compared to oligoarthritis. We found a non-significant tendency of a higher prevalence of the genotype pro1.1 in systemic arthritis (32.4 %) and in rheumatoid factor negative polyarthritis (30.5 %) and a lower pro1.1 genotype in persistent oligoarthritis (20.7 %) and in enthesitis-related arthritis (17 %). Likelihood of the occurrence of genotype IL12-p40 pro1.1 in patients with systemic arthritis (OR 1.722, CI 95 % 1.344-2.615, p 0.0129) and RF-negative polyarthritis (OR 1.576, CI 95 % 1.046-2.376, p 0.0367) compared to persistent oligoarthritis was significantly higher. This was also true for comparison of their homozygous genotypes IL-12p40 pro 1.1 and 2.2 in systemic arthritis (OR 1.779, CI 95 % 1.045-3.029, p 0.0338). However, in Bonferroni correction for multiple hypothesis this was not significant. Conclusion A tendency of a higher prevalence of the genotype IL-12p40 pro1.1 in systemic arthritis and in rheumatoid factor negative polyarthritis was observed but not significant. Further investigations should be done to clarify the role IL-12p40 in the different subtypes of JIA.